Peran Media Berbasis Komputer Dalam Mengembangkan Kognisi Dan Kreativitas Anak Usia Dini - Widyawati Widyawati (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2025)
The development of digital technology has had a significant impact on the world of education, including early childhood 2019–2024. The study results indicate that computer-based media can improve children's cognitive abilities through exploratory activities and interactive problem-solving. Furthermore, the use of computer media also encourages children's creativity in expressing ideas, digital drawing, and creating imaginative thinking patterns through educational games. However, the effectiveness of this media depends heavily on the role of teachers and parents in providing guidance and selecting content appropriate to the child's developmental stage. In conclusion, computer-based media is a potential tool for developing cognition and creativity in early childhood when used in a targeted, contextual manner, and supported by educational guidance.education (PAUD). One widely implemented innovation is the use of computer-based media in the learning process. This article aims to systematically review the role of computer-based media in the development of cognition and creativity in early childhood. The method used is a literature review, reviewing various relevant national and international research findings from